Economical design of H-bridge multilevel inverter drive controlled by modified fast algorithm - Mohammed, Jamal Abdul-Kareem (Microelectronics and reliability, 2016)
Traditional cascaded multilevel inverter needs n DC voltage sources to give 2n+1 levels. As number of levels increased, the amount of switching devices, their proper related drive circuits and their controllers and other components are also increased excessively, making the inverter more complex and costly. A simple and low cost single-phase cascade multilevel inverter with no transformers can be implemented using only single-DC source with n-1 DC sources represented by capacitors and with reduced switches. So, current inverter hardware cost can be reduced abruptly as compared with conventional one. When the number of DC sources is increased, inverter output has higher harmonic content characterized by their transcendental equations that become more complicated and required more time to be solved. New technique is exhibited to find the inverter switching angles by executing modified fast recursive algorithm providing an on-line precise solution for the Harmonic Elimination (HE) problem. The suggested optimized algorithm technique have been used to find optimum switching angles necessary to eliminate any number of lowest order harmonics and maintain the desired fundamental voltage for driving an AC motor. Simulation results of cascade 7-level inverter with single-DC source under the optimized HE stepped waveform technique is used to eliminate the 3rd and 5th harmonics. Prototype design for the proposed inverter loaded by single-phase fan motor is built. •A new simple and low cost cascade 7-level inverter design is implemented.•The inverter uses only 1-DC source with n-1 DC sources as capacitors.•A modified on-line fast algorithm is suggested to control the inverter.•Hardware inverter is reduced by 33% with respect to conventional one.